2013
DOI: 10.1007/s12105-012-0417-9
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of p16INK4A and Cyclin D1 in Benign and Malignant Salivary Gland Tumors: A Study of 44 Cases

Abstract: Salivary gland tumors (SGT) are a heterogeneous group of lesions. There is conflicting data concerning the molecular events involving the tumour suppressor retinoblastoma protein (pRb)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 14 publications
2
24
0
Order By: Relevance
“…Indeed, E6/E7 mRNA viral transcripts were not detected in any of the 92 MECs evaluated including those 14 tumors that were known not to harbor a driver translocation involving MAML2. The absence of high risk HPV using an RNA in situ hybridization approach concurs with its reported absence in those studies using a DNA in situ hybridization approach [15,19]. Outlier studies may reflect, in part, differences in the ability to distinguish between biologically relevant and irrelevant HPV based on methodologies and test interpretation.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Indeed, E6/E7 mRNA viral transcripts were not detected in any of the 92 MECs evaluated including those 14 tumors that were known not to harbor a driver translocation involving MAML2. The absence of high risk HPV using an RNA in situ hybridization approach concurs with its reported absence in those studies using a DNA in situ hybridization approach [15,19]. Outlier studies may reflect, in part, differences in the ability to distinguish between biologically relevant and irrelevant HPV based on methodologies and test interpretation.…”
Section: Discussionsupporting
confidence: 67%
“…reported that about half of all MECs are infected with transcriptionally active high risk HPV, an incidence that rivals its occurrence in the oropharynx. In an effort to substantiate this finding, Jour et al [15] were not able to detect HPV in any of their MECs, but their number of cases was limited (n = 14) and HPV detection was restricted to a DNA in situ hybridization approach. Our study was designed to help resolve the uncertainty surrounding the potential role of HPV in MECs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In surgical specimens of HNSCC, p16 IHC has been shown to be highly sensitive (approaching 100%) for high‐risk HPV, but the specificity is approximately 80% . The decreased specificity can be problematic as p16 overexpression has been noted in a subset of non‐HPV‐associated HNSCCs, and other tumors such as high grade neuroendocrine carcinoma (small cell carcinoma), sinonasal undifferentiated carcinoma, and adenoid cystic carcinoma . In addition, p16 can be expressed in normal tonsillar crypt epithelium and in the epithelium of benign cysts (branchial cleft cysts, lymphoepithelial cyst) …”
Section: P16 Immunohistochemistrymentioning
confidence: 99%
“…[6] Proliferation cell nuclear antibody (PCNA) and Cyclin D1 are proliferation markers that are overexpressed in neoplasms, [7][8][9] and their expression is related to the prognosis.…”
Section: Introductionmentioning
confidence: 99%